Optimization of physical factors affecting the production of thermo-stable organic solvent-tolerant protease from a newly isolated halo tolerant Bacillus subtilis strain Rand - Abusham, Randa Abdelkareem; Raja Abdul Rahman, Raja Noor Zaliha; Salleh, Abu Bakar; Basri, Mahiran (BioMed Central, 2009)
Background: Many researchers have reported on the optimization of protease production; nevertheless, only a few have reported on the optimization of the production of organic solvent tolerant proteases. Ironically, none has reported on thermostable organic solvent-tolerant protease to date. The aim of this study was to isolate the thermostable organic solvent-tolerant protease and identify the culture conditions which support its production. The bacteria of genus Bacillus are active producers of extra-cellular proteases, and the thermostability of enzyme production by Bacillus species has been well-studied by a number of researchers. In the present study, the Bacillus subtilis strain Rand was isolated from the contaminated soil found in Port Dickson, Malaysia.